Choline Phospholipid Metabolites of Human Vascular Endothelial Cells Altered by Cyclooxygenase Inhibition, Growth Factor Depletion, and Paracrine Factors Secreted by Cancer Cells - Noriko Mori; Kshama Natarajan; V. P. Chacko; Dmitri Artemov; Zaver M. Bhujwalla (Molecular Imaging)
Magnetic resonance studies have previously shown that solid tumors and cancer cells in culture typically exhibit high phosphocholine and total choline. Treatment of cancer cells with the anti-inflammatory agent, indomethacin (INDO), reverted the phenotype of choline phospholipid metabolites in cancer cells towards a less malignant phenotype. Since endothelial cells form a key component of tumor vasculature, in this study, we used MR spectroscopy to characterize the phenotype of choline phospholipid metabolites in human umbilical vein endothelial cells (HUVECs). We determined the effect of growth factors, the anti-inflammatory agent INDO, and conditioned media obtained from a malignant cell line, on choline phospholipid metabolites. Growth factor depletion or treatment with INDO induced similar changes in the choline phospholipid metabolites of HUVECs. Treatment with conditioned medium obtained from MDA-MB-231 cancer cells induced changes similar to the presence of growth factor supplements. These results suggest that cancer cells secrete growth factors and/or other molecules that influence the choline phospholipid metabolism of HUVECs. The ability of INDO to alter choline phospholipid metabolism in the presence of growth factor supplements suggests that the inflammatory response pathways of HUVECs may play a role in cancer cell-HUVEC interaction and in the response of HUVECs to growth factors.